A FRAMEWORK TO ASSESS TASK-BASED LANGUAGE LEARNING PERFORMANCE OF STUDENTS VIA ANALYTICAL HIERARCHY PROCESS - SATTAR, WASEEM (2020)
The main purpose of the study was to develop performance assessment framework for task-based Language Teaching (TBLT) students. The framework development was aimed to show real-time performance of students to aid the process of learning. In task-based language learning criterion referenced techniques are often used to assess students’ performance. However, in most cases, teachers/instructors would face issues in determining the appropriate assessment criteria to best evaluate students’ performance. Hence, the study seeks to investigate the significant performance assessment criteria based on relative importance to enhance students’ learning. The study adopted the Analytical Hierarchy Processing (AHP), a quantitative method technique where data was collected through two pair-wise comparative survey questionnaires.